Pengaruh Pemberian Air Susu Ibu dan Fototerapi terhadap Ikterus Neonatorum di Ruang Perinatologi RSUD Pasaman Barat - Yulia M. Nur; Elnita Rahmi; Eliza Eliza (Jurnal Akademika Baiturrahim Jambi, 2021)
Neonatal jaundice is a common problem in the care of normal newborns. West Pasaman Regional Hospital data states that in 2018 there were 41 cases of neonatal jaundice out of 369 deliveries. The research objective was to determine the effect of exclusive breastfeeding and phototherapy on the incidence of neonatal jaundice. The research method is retrospective, namely conducting research on past events. The research was conducted at RSUD Pasaman Barat with a population of 20 people. Sampling was done by total sampling technique, so that the sample size is 20 people. Data collection was carried out by means of observation at the West Pasaman Regional Hospital. The approach used is cross sectional, namely independent and dependent data collection is done at the same time. The data that has been collected is then processed manually and analyzed by computerized univariate and bivariate analysis. This type of research is descriptive with a cross sectional design. The study population was all babies in West Pasaman Regional Hospital with a total of 41 people, the sample size was determined by the total sampling so that the sample was 41 people. The data was collected by means of a documentation study using a checklist. Data processing was carried out by univariate computerization. The results showed that as many as 13 respondents (31.7%) were breast-fed, 63.4% were carried out with phototherapy and 24.4% of respondents had neonatal jaundice. Based on the bivariate analysis obtained p value 0.049 (Breastfeeding) and 0.001 (Phototherapy). The results of the Chi Square test, it can be concluded that there is an effect of breastfeeding and phototherapy on the incidence of neonatal jaundice